3(a²-2ab)-2(3ab-b²)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 22:27:16
3(a²-2ab)-2(3ab-b²)3(a²-2ab)-2(3ab-b²)3(a²-2ab)-2(3ab-b²)3a²-6ab-
3(a²-2ab)-2(3ab-b²)
3(a²-2ab)-2(3ab-b²)
3(a²-2ab)-2(3ab-b²)
3a²-6ab-6ab+2b²
=3a²-12ab+2b²
3ab·(a²b-ab²+ab)-ab²(2a²-3ab+2a)
3ab(a²b-ab²-ab)-ab²(2a²-3ab+2a)
计算:2ab[(2ab)²-3b(ab+a²b)-ab²]
合并同类项5a²b-3ab-4ab²+7ab-2ab²
3(a²-2ab)-2(3ab-b²)
7a²b+(-4a²+5ab²)-(2a²-3ab²)
2a²+3ab+b²-a²-ab-2b²,其中a²-b²=2,ab=-3
已知a²-ab=3,ab+b²=-5,求代数式a²+b²与a²-2ab-b²
如果a²+ab=4,ab+b²=-1,a²+b²等于多少?那么a²+3ab+2b²等于多少?
a²+ab=4 ab+b²=-1 那么a²-b²=( ) a²+3ab+2b²=( )
如果a²+ab=4,ab+b²=-1.那么a²-b²等于多少?a²+3ab+2b²等于多少
-(a²-2ab)×9a²-(9ab³+12a^4b²)÷3ab=
计算:4a²+3b²-4a²+2ab-4b²
2(a²-ab)-4(2a²-3ab)-2【a²-(2a²-ab+b²)】 计算
数学题3a-²b×2ab-²
3a²+7ab+2b²
3(a²+2b²)与8ab
3a²b-[2ab²-(2ab-3a²b)+ab]+3ab²,其中a=1/2,b=2